PENGARUH KECERDASAN EMOSI TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN SENI BUDAYA SMP - Purnaningtyas, Arum; Suharto, Suharto (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2010)
This research purposes to know : (1) Correlation between emotional intelligence and students achievement in the culture art lesson study, (2) Influence of emotional intelligence to students' achievement in the culture art lesson study, (3) contribution of emotional intelligence to students achievement in the culture art lesson study. The method used in this research is the quantitative correlation action research using ex post facto technique. Data collection techniques used were documentary study and questionnaire. Techniques of data analyze using product moment correlation, regression correlation, and determination coefficient. The result showed that : (1) There was a significant correlation between emotional intelligence and students' achievement in the culture art lesson study (2) From the regression Ã‚Â Y = 60,660 + 0,169X means that if emotional intelligence values progressed 1 point, so the students' achievement values progressed 0,169 points, (3) Contribution of emotional intelligence to students' achievement in the culture art lesson study were 12,2% and 87,8% supported by other factors. Based on the above result, so the teachers and schools team suggested for giving accommodation, and implementation to emotional intelligence factor in the education.